Infanticide : expert evidence and testimony in child murder cases, 1688-1955 - Dixon, Rachel (Lecturer in Law) (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Infanticide examines medical expert evidence in infanticide cases, focusing specifically on the shifting notion of 'certainty' in medical testimony. Beginning in the early modern period and concluding in the mid-twentieth century, it considers how courts determined whether an infant has died from natural causes or other reasons, including violence. This book will be of great interest to students and scholars Criminology, Law and History"--
OCLC-licensed vendor bibliographic record.
Keywords: Infanticide -- History; Evidence, Expert -- History; HISTORY / General; SOCIAL SCIENCE / Criminology